Study of Rhizosphere Bacteria on the Coast of Mempawah Mangrove as Bioremediation Agents - Aini Sulastri; Jumiati Jumiati; Putranty Widha Nugraheni; Leonardus Sandy Ade Putra; Eka Kusumawardhani (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
The production and accumulation of organic matter in the mangrove ecosystem allow this area to be rich in microbes and potentially develop as a source of various extracellular enzymes. This research aims to create effective microorganisms as bioremediation agents and determine the composition of the types of bacteria found in mangrove areas, sediments, leaf litter, stems, and mangrove plants. Sediment and vegetation were obtained as samples for being diluted and isolated, then spread onto media to get a single pure colony using Zobell 2216 method. The virgin territory formed is distinguished by characterization using macroscopic observations. It was found that the composition of bacteria isolated from the mangrove area contained 59 isolates with various visible characteristics consisting of 20 isolates of sedimentary bacteria, 27 isolates of bacteria on stems, and 12 isolates of bacteria derived from mangrove leaves. Bacterial isolates S08, B27, and D04 have the potential for the bioremediation of Hg metal. Bacterial isolates S58, B35, and D13 have potential for Pb bioremediation, while bacterial isolates S27, B35, and D12 have potential as Fe bioremediation agents.